Cover Feature: Synthesis of Spirocyclic Cyclobutenes through Desulfinative Spirocyclisation of gem‐Bis(triflyl)cyclobutenes (Chem. Eur. J. 33/2022). Issue 33 (26th May 2022) - Hoshikawa, Shoki; Yanai, Hikaru; Matsumoto, Takashi
Abstract : An effective two‐step synthesis for spiro[cyclobutene‐1, 9′‐fluorene] has been developed that allows the arrangement of substituents on three mutually orthogonal axes (triaxes), represented as the right/left hand of Fleming's rules. This unique molecular scaffold leads to new designs of functional small molecules and macromolecules. More information can be found in the Research Article by S. Hoshikawa, H. Yanai and T. Matsumoto (DOI: 10.1002/chem.202200704 ).